Identifikasi Kandungan Gizi Uwi Asal Wakatobi - La Harimu; Syahrir, Romeo; Haeruddin; Mulyana, Wa Ode; Mandasari, Eka Cahyana (Balitbangda Kota Baubau, 2024)
One of the potential plants due to its good nutritional value in Wakatobi Regency is Dioscorea alata L, locally known as uwi ifi and opa. This plant has been cultivated for a long time, but recently it has started to be neglected due to the changing food consumption patterns of the community, which tend to shift towards rice-based foods. To preserve and optimally utilize this uwi, it is necessary to identify the diversity of uwi types and their nutritional content. Data on the characteristics of these uwi types are obtained through direct observation of their shape, skin surface, texture, and the color of the inner tuber, combined with standard literature. Direct observation is conducted in two ways: directly on the uwi plants in the field or on the land, and observation in the laboratory. Measurement of nutritional content or chemical compound content is conducted in the biology laboratory of FMIPA UHO. The results of the study showed that of the 20 types of uwi in Wakatobi Regency, namely 16 from uwi ifi and 4 from uwi opa that were identified to have various shapes, colors, and textures, both uwi ifi and opa, namely bulbs in round, cylindrical, javelinous, oval and irregular shapes. The shape of the surface of the tuber is wrinkled, rough, flat and porous. The skin color in the tuber and the color of the tuber flesh are white, milky white, purple, and beige. Of the 16 types of uwi ifi and 13 parameters that were measured best in ifi kadola with carbohydrate content (41.74%), glucose (0.38%), crude fiber (12.39%), protein (3.41%), fat (0.906%), water (58.81%), ash (4.52%), phosphate (774.36 mg/kg), calcium (538.09 mg/kg), vitamin C (5.22 mg/kg), vitamin A (0.22 μg/100 grams), vitamin B1 (0.153 mg/kg), and iron (5.949 mg/kg). Among the best types of opa is the larantuka type with a carbohydrate content of (36.0%), glucose (0.23%), crude fiber (9.94%), protein (2.90%), fat (0.713%), water (41.07%), ash (3.34%), phosphate (594.87 mg/kg), calcium (338.09 mg/kg), vitamin C (8.11 mg/kg), vitamin A (0.38 μg/100 grams), vitamin B1 (0.162 mg/kg), and iron (3.795 mg/kg). Thus, the two types of uwi found in Wakatobi Regency have great potential to be used as a source of local and national food as well as for nutritious lunch ingredients with an interesting touch of processing.